2002
DOI: 10.1007/s00167-001-0266-7
|View full text |Cite
|
Sign up to set email alerts
|

Tightening elongated ACL grafts by application of bipolar electromagnetic energy (ligament shrinkage)

Abstract: In ACL transplants showing elongation with functional deficit but no interruption of structure (Marburg Arthroscopic Score type III) there is the possibility of reinsertion, augmentation, or revision ACL reconstruction to stabilize the joint. Bipolar electromagnetic energy can be used to induce the tightening of elongated ACL transplants. We examined 14 patients with a secondary instability after ACL transplantation (mean 23.6 months). During arthroscopy a type III transplant without signs of nonisometric posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
7
0
2
Order By: Relevance
“…L'alternative à une ligamentoplastie itérative est la remise en tension du ligament croisé. Dans ce but, Carter et al [15], Spahn et Schindler [16] et Halbrecht [17] ont eu recours au shrinkage. Cette technique consiste à appliquer une sonde thermique sur le ligament afin d'obtenir, par brûlure, une rétraction cicatricielle.…”
Section: Discussionunclassified
“…L'alternative à une ligamentoplastie itérative est la remise en tension du ligament croisé. Dans ce but, Carter et al [15], Spahn et Schindler [16] et Halbrecht [17] ont eu recours au shrinkage. Cette technique consiste à appliquer une sonde thermique sur le ligament afin d'obtenir, par brûlure, une rétraction cicatricielle.…”
Section: Discussionunclassified
“…Lysholm scores improved from 35.9 to 88.5, and tibial translation was reduced from 13 to 2 mm. 22 Most recently, Carter et al reported their short-term results on a series of 18 patients, including 7 grafts and 11 partial tears. 4 At 20-month follow-up, 11 of 18 patients had gone on to failure (6/7 grafts and 5/11 partial tears).…”
Section: Acl Shrinkage Studiesmentioning
confidence: 98%
“…Spahn and Schindler [23], observed lax but intact ACL grafts in 14 patients undergoing revision arthroscopy after ACL reconstruction (eight patellar tendon grafts, six double bundle semitendinosis reconstructions). The RF treatment was with a bipolar probe at 284 W ''until the ligament was tight'' and for ''approximately 60 s. Central portions of the ligament were treated in the first step and the periphery in the second.''…”
Section: Case Seriesmentioning
confidence: 99%